Journalism, public service and BBC News Online - Allan, Stuart and Thorsen, Einar (2010)
"First, we examine the actual launch of BBC News Online, devoting particular attention to the ways in ways in which the Corporation’s public service commitments shaped its remit, in general, as well as its conception of online journalism, in particular. Second, we proceed to discern a number of the interactive features associated with this rapidly growing news provision over the first ten years of the site’s operation. In offering an appraisal of the guiding imperatives of interactivity – not least with regard to user-generated content – we aim to identify for purposes of elaboration several issues warranting further investigation." [Information des Anbieters]
https://katalog.adlr.link/Record/finc-80-15334